ANALISIS KRITIS TERHADAP PERENCANAAN PEMBANGKIT LISTRIK TENAGA SURYA (PLTS) TIPE PHOTOVOLTAIC (PV) SEBAGAI ENERGI ALTERNATIF MASA DEPAN - Supari Muslim; Khusnul Khotimah; Alfiantin Noor Azhiimah (Rang Teknik Journal, 2020)
Electrical energy needs will continue to increase in line with the needs of the community, both on an industrial scale and the household in general. On the other hand the supply of fuel oil and coal as a driving force for power station centers is increasingly depleting. Because of that, a lot of research is needed to obtain renewable energy, as well as being environmentally friendly. One of the abundant energy sources in Indonesia is water resources. Utilization of water resources can be done by building a Micro Hydro Power Plant (MHPP). Based on the results of the study through literature studies, from as many as 13 journals (in 2009-2019) it can be seen that in Indonesia there are still many regions that have not yet received electricity supply from PT. PLN, with the following reasons: (1) the availability of PT. PLN is not enough to meet the needs of the community; and (2) many areas are located far from the PLN electricity network; and (3) many regions whose infrastructure does not support the expansion of the PLN electricity network. This condition is hampering the speed of economic development in the regions concerned. The study found that: (1) there were 13 points of water resources that could potentially be built by MHPP with electrical power varying depending on the amount of water resources concerned; and (2) from the results of the study, there are a number of studies that have been implemented and some of them are still in preparation for the construction of the MHPP.